À qui appartient l'obligation de fiduciaire à l'égard des autochtones ? - Boivin, Richard (Les Cahiers de droit, 1994)
The Supreme Court of Canada held in Guerin and Sparrow that the Crown has a fiduciary obligation to protect the interests of aboriginal people. While this obligation undoubtedly applies to the federal Crown, its application to the provincial Crowns remains to be determined. This article attempts to set out the parameters of the Crown's fiduciary obligation to aboriginal people. Based on historic, legislative and jurisprudential analysis, the author submits that the fiduciary obligation is an exclusive federal Crown responsibility.